On the type series of Stenosigma humerale Giordani Soika with the description of a new species (Hymenoptera, Vespidae, Eumeninae) - Hermes,Marcel G. (2016)
ABSTRACT A new species, Stenosigma quechua Hermes & Ferreira sp. nov., is described from specimens previously included in the type series of Stenosigma humerale Giordani Soika, 1990. Details on the differences between the two species as well as comments of taxonomic implications are presented.